Die Erzählung von Jiftach und seiner Tochter (Ri 11,29-40). Eine empirische Lesestudie - Malmes, Judith (2009)
The biblical narrative on Jiftach and his daughter (Jdg 11:29-40) contains many blank spaces and ambiguity which the reader has to fill and interpret herself. Since everyone reads the text with differing expectations and premises, the understanding by each reader will always be different. While there are some interpretative text studies, the interpretation and impression of today’s readers are rarely being investigated. The aim of the study is to examine to what extent the specific narration style influences the reader’s interpretation process and appraisal of the plot and characters. At first, a separate analysis of the text will be conducted to illustrate the blank spaces and the narration style. This is followed by a presentation of the findings of the empirical study and a concluding reflection of the results.
Keywords: Bibel; Rezeptionsästhetik; Textverstehen; Erzähltheorie